Land- and pool-based intervention in female fibromyalgia patients: A randomized-controlled trial - Acosta-Gallego, Agusti; Ruiz-Montero, Pedro Jesús; Castillo-Rodríguez, Alfonso (Turkish Journal of Phisical Medicine and Rehabilitation, 2019)
Objectives: The aim of this study was to assess the effect of a standard physical rehabilitation intervention (SPRI) program, in pool-based (SPRI-P) and land-based (SPRI-L) environments, applied to female fibromyalgia (FM) patients with mild-to-moderate symptoms during a period of 20 weeks. Patients and methods: Between September 2016 and September 2017, a total of 73 female FM patients (mean age 48.2 +/- 6.8 years; range, 30 to 59 years) who suffered from FM were included in this study on a voluntary basis. The SPRI program was applied to the patients for 20 weeks. The severity of FM was assessed using the Fibromyalgia Impact Questionnaire. The dependent variables including self-perceived pain, perceived fatigue, aerobic capacity, depressive symptoms, and the overall impact of FM were evaluated. Results: Self-perceived pain, perceived fatigue, overall impact of FM (p<0.05) and depressive symptoms (p<0.001) of the participants in the SPRI-P program decreased in the post-test values, compared to the pre-test values. Using the SPRI-L program, a significant improvement in the aerobic capacity (maximum consumption of relative oxygen and distance in meters), overall impact of FM (p<0.05), and depressive symptoms (p<0.01) was observed. Conclusion: Our study results indicated that the SPRI-P program yielded improvements in patients with FM in self-perceived pain, perceived fatigue, depressive symptoms, and overall impact, as well as improving the aerobic capacity. In addition, in the SPRI-L program, the participants increased their capacities, self-perceived pain, and overall impact of FM.
Keywords: female; fibromyalgia; pain; physical activity; interventional; program; JCR; Scopus